Messages on Family and Community Medicine and Primary Care addressed to Family Doctors, residents, medical students, health and education managers - Anderson, Maria Inez Padula (2021)
In the commemorative year of 40 years of the Brazilian Society of Family and Community Medicine (SBMFC) and 45 years of Family and Community Medicine (FCM) as a specialty in Brazil, this article, in the form of interviews, provides messages from guests and professionals who represent the past, present and future history of FCM and SBMFC here. They are professionals who relate to the history of these 40/45 years, considering some of their roles in FCM and SBMFC in that period. Their relations with FCM and SBMFC can be read in the Editorial of this commemorative issue. Messages about FCM and primary health care (PHC) are directed at FCM residents, family and community doctors, doctors working in PHC, medical students. health and education managers and the general population.